Referral Centre Experience with Infected Abdominal Aortic Endograft Explantation. (January 2023) - Khalid, Wajih; Puges, Mathilde; Stenson, Katherine; Cazanave, Charles; Ducasse, Eric; Caradu, Caroline; Berard, Xavier
Abstract : Objective: The increasing use of endovascular aneurysm repair (EVAR) appears to be associated with the burden of vascular endograft infections. Complete stent graft explantation is recommended but leads to significant mortality. This study aimed to assess the technical challenges, complications, and mortality rate following infected endograft explantation. Methods: Patients who underwent abdominal aortic endograft explantation for infection at the Bordeaux University Hospital from July 2008 to December 2020 were included retrospectively in this single centre observational study. The diagnosis was established based on the MAGIC criteria. The primary endpoint was 30 day mortality. Secondary endpoints were 90 day and in hospital mortality, survival, and re-infection. Results: Thirty-four patients were included, median age 69 years (interquartile range [IQR] 65, 76), with four (12%) treated as an emergency. The median time from EVAR to explantation was 17.5 months (4.5 – 36.3). In situ reconstruction was carried out with prosthetic grafts in 24 patients (71%, including 23 antimicrobial grafts combining silver and triclosan), and biological grafts in 10 (five femoral veins, four arterial allografts, three bovine patches, one biosynthetic graft). Seventeen aorto-enteric fistulae (AEnF) were addressed with direct repair of the intestinal tract ( n  = 10/17; 59%) or resection and anastomosis ( n  = 7/17; 41%). The culture was polymicrobial in 12 patients (35%) and remained sterile in four (12%). The 30 day and in hospital mortality rates were 21% ( n  = 7) and 27% ( n  = 9). Twenty-five patients (73%) presented with early post-operative complications, requiring 16 revision procedures (47%). Over a median follow up of 16.2 months (IQR 8.3, 33.6), the mortality rate was 35% ( n  = 12; 11 aortic related; 32%), with two re-infections (6%), both after biological reconstruction (one for an AEnF). Conclusion: Early morbidity and mortality remain high after complete infected endograft explantation, even in a high volume centre. Comparison with other treatment modalities in large multicentre cohorts might be of interest.